A Comparative Study on Emission and Performance Characteristics of Neem Biodiesel Under Various Load Conditions - D.S.Balaji; S.Prabhakaran; K.Umanath; V.Kurinji; A.R.Sivaram; C.Joel (International Journal of Psychosocial Rehabilitation, 2020)
In the current energy scene of fossil fuel, renewable energy sources such as biodiesel, bioethanol, biomethane, and biomass from wastes or hydrogen have become the subjects of great interest. The present study was intended to consider aspects related to the testing of performance and emission of biodiesel from Neem oil and additives investigating its fuel properties. Biodiesel can make a major contribution in the future if it meets the few percent of petroleum and it can provide improved fuel properties lower emission of unburned hydrocarbons, carbon monoxide but higher level of oxides of nitrogen in biodiesel but eventually can be reduced by using selected additives in biodiesel. Comparative study on properties of diesel and biodiesel fuels with/without presence of water and nanoparticle additives have been made. It was seen that blending nano particles with these type of emulsion fuel would improve performance and reduce emission of an IC Engine characteristics.